Effect of Good Corporate Governance, Accounting Conservatism And Size of Company Earnings Management With Managerial Ownership As In Developing Countries Moderating Variables Asean (Indonesia, Malaysia And Thailand) Period 2015-2019 - Andriani Andriani; Hamidah Hamidah; Harya Kuncara Wiralaga (International Journal on Advanced Science, Education, and Religion, 2021)
The study was conducted on 40 manufacturing companies listed on the Stock Exchange (Indonesia, Malaysia and Thailand) for the 2015-2019 period. The research objective was to determine the effect of good corporate governance, accounting conservatism and firm size on earnings management with managerial ownership as a moderating variable.The results of this study indicate that good corporate governance has no significant effect on earnings management, accounting conservatism has a significant effect on earnings management, firm size has a significant effect on earnings management, managerial ownership cannot moderate between good corporate governance and earnings management, managerial ownership cannot moderate conservatism. Accounting for Earnings Management, Managerial Ownership can moderate the size of the company to earnings management in Indonesia, Malaysia and Thailand. Earnings management is a manager's effort in their financial statements where actions are taken by company management with the aim of increasing or decreasing the company's profits in the financial statements.